Inside man [videorecording (DVD)] - Abeckaser, Danny A.; Kondilopoulos, Kosta; Stefanski, Kyle; Koss, Bryan, 1981-; Cohen, Lionel (Composer); Antoine, Arielle; Hirsch, Emile, 1985-; Cannavale, Jake; Hale, Lucy, 1989-; Greene, Ashley, 1987-; Laresca, Vincent; Davi, Robert (Vertical Entertainment, 2023)
Inside Man follows a disgraced police detective seeking redemption by going undercover to expose a violent and bloody crime syndicate. But as he sinks deeper into the mob and more bodies drop, the price for absolution may be higher than he can pay.